2016
DOI: 10.2147/ijn.s101872
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the therapeutic potential of hypoxia-inducible factor-1α small interfering RNA in malignant melanoma delivered via folate-decorated cationic liposomes

Abstract: Malignant melanoma (MM) represents the most dangerous form of skin cancer, and its incidence is expected to rise in the coming time. However, therapy for MM is limited by low topical drug concentration and multidrug resistance. This article aimed to develop folate-decorated cationic liposomes (fc-LPs) for hypoxia-inducible factor-1α (HIF-1α) small interfering (siRNA) delivery, and to evaluate the potential of such siRNA/liposome complexes in MM therapy. HIF-1α siRNA-loaded fc-LPs (siRNA-fc-LPs) were prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The use of delivery carriers may improve the efficacy of HIF-related therapeutic agents following systemic administration, by overcoming the pharmacokinetic and stability issues. The best example of this is in the delivery of gene therapy targeting HIFs, which have previously been shown to modulate cellular responses in hypoxia-related diseases (Post et al, 2007 ; Tal et al, 2008 ; Wang et al, 2008 ; del Rey et al, 2009 ; Chen et al, 2016 ). The delivery of small interfering RNA (siRNA) remains a challenge because of the lack of suitable vectors.…”
Section: Targeting Hif-regulated Pathways In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…The use of delivery carriers may improve the efficacy of HIF-related therapeutic agents following systemic administration, by overcoming the pharmacokinetic and stability issues. The best example of this is in the delivery of gene therapy targeting HIFs, which have previously been shown to modulate cellular responses in hypoxia-related diseases (Post et al, 2007 ; Tal et al, 2008 ; Wang et al, 2008 ; del Rey et al, 2009 ; Chen et al, 2016 ). The delivery of small interfering RNA (siRNA) remains a challenge because of the lack of suitable vectors.…”
Section: Targeting Hif-regulated Pathways In Ramentioning
confidence: 99%
“…Although viral vectors have shown to be effective, the concerns surrounding their safety have limited their application. Therefore, non-viral vectors have been investigated as an alternative delivery platform for HIF gene delivery—including liposomes (Wang et al, 2008 ; Chen et al, 2016 ) and polymer-based nanoparticles (Liu et al, 2009 ). For example, Wang et al demonstrated that PEGylated liposomes loaded with doxorubicin and antisense oligonucleotides targeted to HIF-1α mRNA was able to effectively deliver the active agents into tumor cells on nude mice bearing xenografts of multidrug-resistant human ovarian carcinoma (Wang et al, 2008 ).…”
Section: Targeting Hif-regulated Pathways In Ramentioning
confidence: 99%
“…compared to the free type [35][36][37]40,45,46,50,56,57,62]; however, an increase in toxicity was observed in another study [41]. By the way, a number of studies have not examined the toxicity of liposome-encapsulated drugs in comparison to the free form [38,39,[42][43][44][47][48][49][51][52][53]55,[58][59][60][61][63][64][65][66][67].…”
Section: Interventions and Results Of Interventions Interventions Rel...mentioning
confidence: 99%
“…These hypoxic prodrug agents may significantly alleviate off-target effects of the biological therapy by limiting active drug to hypoxic tissue and only inhibiting HIF-1α in hypoxic tissues. Gene therapy targeting HIF-1α may also be effective for therapy in hypoxia-related diseases as well (Tal et al, 2008; Wang et al, 2008; del Rey et al, 2009; Chen et al, 2016). In addition, the therapeutic benefits of HIF-1α inhibitors would be maximized in the presence of delivery carriers that eliminate pharmacokinetic and stability problems and minimize potential systemic toxicity.…”
Section: Targeting Hif-1α In Fibrosismentioning
confidence: 99%
“…In addition, the therapeutic benefits of HIF-1α inhibitors would be maximized in the presence of delivery carriers that eliminate pharmacokinetic and stability problems and minimize potential systemic toxicity. For example, liposomes and nanoscale-based drug delivery systems may be applied as a delivery assistant for HIF-1α gene therapy (Wang et al, 2008; Chen et al, 2016). The most successful example of a successful liposomal drug delivery system may be that for Amphotericin B, which has been widely applied in the clinic for treating invasive fungal infections.…”
Section: Targeting Hif-1α In Fibrosismentioning
confidence: 99%